2022
DOI: 10.1177/21582440221097897
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship Between Achievement Motivation and Entrepreneurial Intention: A Conditional Process Model of Entrepreneurship and Gender

Abstract: This study focused on the roles of entrepreneurship and gender in the relationship between achievement motivation and entrepreneurial intention. Specifically, we tested a moderating role of gender and examined the moderated mediating role of entrepreneurship by gender in the relationship between achievement motivation and entrepreneurial intention. Based on the secondary data from the 2017 Korea Entrepreneurship Survey on 10,000 people, a conditional process model 15 (Hayes’ PROCESS macro) analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 81 publications
(132 reference statements)
1
6
0
Order By: Relevance
“…Jumbri et al (2019) found that women entrepreneurs are motivated by a high need for achievement, a slightly high need for power and a moderate need for affiliation. Kong & Choo (2022) also confirmed that the indirect effect of achievement motivation on entrepreneurship was stronger for women than for men. Understanding agricultural students' motivation towards entrepreneurship is important since that will assist in the identification of pertinent mechanisms to address their position for the better.…”
Section: The Role Of Gendersupporting
confidence: 63%
“…Jumbri et al (2019) found that women entrepreneurs are motivated by a high need for achievement, a slightly high need for power and a moderate need for affiliation. Kong & Choo (2022) also confirmed that the indirect effect of achievement motivation on entrepreneurship was stronger for women than for men. Understanding agricultural students' motivation towards entrepreneurship is important since that will assist in the identification of pertinent mechanisms to address their position for the better.…”
Section: The Role Of Gendersupporting
confidence: 63%
“…This is highlighted in the study by Carlianne et al (2016), which considers that among mothers with young children, the probability of choosing to work as employees or as self-employed remains very low. Also, the recent study by Kong and Choo (2022) shows that women’s entrepreneurial intention and motivation remain far below those of their male counterparts because of their perception of risk and their fear of failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, from the IT services perspective, innovation is defined mainly as operational improvements (Govindan, 2023; Rodríguez‐Espíndola et al, 2022). Many studies clearly mentioned the significant impact of ICT on the productivity of business organizations; therefore, many studies considered ICT‐based innovations for adoption and diffusion (Geng et al, 2023; Kuan & Chau, 2001; Mohanty & Mishra, 2020). Many models have been recommended in the adoption of ICT research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, while there are many similarities between the TOE framework and the diffusion of innovation theory, in the TOE framework, the environmental context has been included, which is not present in the diffusion of innovation theory (Premkumar & Roberts, 1999; Mohanty & Mishra, 2020; Geng et al, 2023) Subsequently, the TOE framework has been supported by reliable empirical studies and has a strong theoretical foundation (Chong et al, 2009; Govindan, 2023; Mohanty & Mishra, 2020). Another reason is that the TOE framework has been able to overcome the dominance of the technical perspective and is useful as an analytical tool to differentiate between the essential abilities of an innovation and the motivations, capabilities as well as it provides a wider environmental perspective for the adopting firm (Mohanty & Mishra, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%